Atributos do solo e palhada remanescente de forrageiras de inverno submetidas a diferentes manejos em sistema de integração lavoura-pecuária - Vengen, Andressa Perini (2018)
The objective of this work was to evaluate the effect of grazing frequency on winter forage under a system of crop-livestock integration on the chemical and physical properties of the soil and on the dynamics and release of nutrients from the remaining straw. The experiment was carried out under field conditions, during the 2016/2017 harvest at the Experimental Station Professor Antônio Carlos dos Santos Pessoa, belonging to the State University of the West of Paraná, Campus Marechal Cândido Rondon - PR, in soil classified as LATOSOLO VERMELHO Eutroferric de very clayey texture. The experimental design was a randomized complete block design with three replicates. The plots were formed by the combination of the A and B bands. The A ranges comprised the forage species tested, consisting of black oats BRS 139, black oats IPR 61, white oats IPR Esmeralda, Triticale 111 TPolo and the consortium of Triticale 111 TPolo with oats white Emerald IPR. In the B bands, transversal to the bands A, were allocated the management: without grazing, one grazing and two grazing. The levels of total nitrogen, total organic carbon, organic matter, macroporosity, microporosity, total porosity and density were evaluated after harvesting the soybean cultivated in succession. The dry matter yield of the forages and the release of nutrients C, N, P, K from the residual straw were also evaluated. The forage plants used for grazing resulted in different levels of total nitrogen and organic matter in the soil when submitted to grazing, where the soil cultivated with Triticale 111 TPolo superior to the Iapar 61 oats for both attributes. The highest levels of total nitrogen, total organic carbon, organic matter and C / N ratio were observed in the superficial layer, regardless of the management used. The macroporosity of the soil was altered according to the cultivars and the soil layers. In the 0-0.05 m layer, the consortium of Esmeralda and Triticale 111 TPolo oats resulted in a lower volume of macropores. The microporosity and total porosity were lower in the layers of 0.05-0.10 m and 0.10-0.20 m in the areas cultivated with Triticale 111 TPolo under two grazing. The lowest soil density was found in the superficial layer, regardless of the management or the forage plant used, which indicates the absence of compaction by animal trampling. The IPR Esmeralda oat showed the highest productivity of dry matter remaining when not grazed, whereas Triticale 111 TPolo obtained the highest averages when submitted to grazing. The amount N, P and K released from the remaining dry matter, regardless of the adopted management, decreased over time. Potassium was the nutrient that presented the most accelerated release. The winter forages, when submitted to two grazing, reduce the amount and increase the half-life of the nutrients. At 120 days after foraging desiccation, the treatment of the IPR Esmeralda oat under grazing presented lower dry matter, C, N, P and K (21%, 20%, 19%, 17%, and 1% respectively) in the remaining material. Triticale 111 TPolo under the same management presented 16%, 15%, 12%, 6% and 2% for the respective variables. Triticale 111 TPolo, when subjected to grazing, is more efficient in nutrient cycling, providing 197, 38 and 231 kg ha-1 of N, P and K, respectively. In SILP, forage species are able to cycle the nutrients and make it available to crops in succession, which reduces fertilizer costs and contributes to the rational use and sustainability of the system.